Ramicrusta invasive alga causes mortality in Caribbean coral larvae - Cayemitte, Kayla; Aoki, Nadège; Ferguson, Sophie R.; Mooney, T. Aran; Apprill, Amy (Frontiers in Marine Science, 2023)
The settlement of coral larvae is an important process which contributes to the success and longevity of coral reefs. Coral larvae often recruit to benthic structures covered with crustose coralline algae (CCA) which produce cues that promote settlement and metamorphosis. The Peysonneliaceae Ramicrusta spp. are red-brown encrusting alga that have recently become abundant on shallow Caribbean reefs, replacing CCA habitat, overgrowing corals and potentially threatening coral recruitment. In order to assess the threat of Ramicrusta to coral recruitment, we compared the survival and settlement of Porites astreoides and Favia fragum larvae to 0.5 – 2 mg ml-1 solutions of Ramicrusta sp. or CCA as well as sterile seawater (control). In all cases larval mortality was extremely high in the Ramicrusta treatments compared to the CCA and control treatments. We found 96% (± 8.9% standard deviation, SD) mortality of P. astreoides larvae when exposed to solutions of Ramicrusta and 0 - 4% (± 0 - 8.9% SD) mortality in the CCA treatments. We observed 100% F. fragum larval mortality when exposed to Ramicrusta and 5 – 10% (± 10 – 20% SD) mortality in the CCA treatments. Settlement or surface interaction of larvae in the CCA treatments was 40 - 68% (± 22 - 37% SD) for P. astreoides and 65 - 75% (± 10 - 19% SD) for F. fragum. Two P. astreoides larva that survived Ramicrusta exposure did settle/surface interact, suggesting that some larvae may be tolerant to Ramicrusta. These results suggest that Ramicrusta is a lethal threat to Caribbean coral recruitment.